The Application of Presentation Method to Increase Student’s Ability in Explaining Cases - ismawati, ismawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
This study was carried out with the purpose to measure the effectiveness of Presentation Method in increasing students’ ability in explaining cases. This study is quantitative research. Quantitative research was used as the mean in collecting the data. The population of this study was the students at the Second Grade of MAN Model Sorong in the years 2014/2015, by the number were 208 students. The sample of this study was the students of XI IPA 2 by the number were 30 students and XI IPA 3 by the number were 28 students. The writer used pretest- posttest control group design of true experimental design in this study. The result of study was presented into tables and had explained by percentage. In analyzing data the writer used the application of SPSS 18. The result of this study showed that there was an increasing score of students at experimental group. The mean pretest of both experimental group and control group before were 45. Then after treatment was given to experimental group the mean was 80. But the mean of control group was 40,25. It means that Presentation Method is effective to increase students’ ability in explaining cases. The result of this study showed that the T value > T table = 17.667 > 2.093. It means that the hypothesis of this study was accepted. The writer concluded that Presentation Method can increase student’s ability in explaining the cases.